Tożsamość we współczesnej instytucji: zarządzanie poprzez przestrzenie upodmiotowienia - Melosik, Zbyszko (Studia Edukacyjne, 2020)
The aim of the article is to reconstruct the emerging patterns of controlling people in contemporary institution which is connected with creating the spaces of empowerment. The management of people is ensured through concertive control the essence of which is related to mutual „watching” of each other by the teams members. At firstsight the concertive control is much less oppressive than in the past direct top to the bottom control. However, in practice it is more effective control as institution aims and values are realized by people which feel to be empowered thanks to lack of direct presence of top managers. In concertive control workers do not seem to be aware that they are only of an instrument of top managers’ power.